Representações dos alunos de um cieja sobre o processo de ensino-aprendizado de língua inglesa - Corte, Luciane Cristina (2013)
This research aims at investigating the representations of teaching and learning process of the English language of the CIEJA`s students from level 4. This study was conducted in the teacher-researcher’s classroom with 6 students of the 4th level of Young and Adult’s Education (CIEJA) of a public school in São Paulo. The data were collected from March to September of 2012 by questionnaires, minute papers and interviews. The social representations were supported by the notions of Moscovici (1961; 2003)`s Theory, Jodelet (1989; 2001) e Celane e Magalhães (2002). It also focuses on the learning theories (behaviorism, cognitivism and socio-interactionism) and on the teaching and learning process of a foreign language in Brazil proposed by Parâmetros Curriculares Nacionais para o Ensino de Língua Estrangeira (1998). The results showed that the representations of the learners about English teaching-learning process is that they are conscious of importance that language in present context. The results helped, also, identify the different levels of reflection, crucial for the process of self-awareness, which led, on some occasions, to the (re) formulation and reconstruction of the pedagogic action